1900 Mass. Acts 150, An Act to Regulate the Shooting of Black Duck, Geese, Brant and Other Aquatic Birds in Plymouth Harbor or Bay, ch. 209, § 1 - (:unkn) unknown (General Publisher, 1900)
Whoever within the limits of Plymouth harbor or bay, . . . shoots at or kills or pursues a black duck, goose, brant or other aquatic bird, by the use of any sneak boat, raft, floating box or device of like description, not including what is known as an ordinary dory or row boat, or by the use of any pivot gun or swivel gun, or any other firearm not usually held at and discharged from the shoulder, shall be punished by a fine of not less than ten nor more than fifty dollars.
--
Keywords: HUNTING REGULATION